The Differences of Malondialdehyde Serum Level, Expression of Tumor Necrosis Factor Alpha and Vascular Endothelial Growth Factor, and the Area of Endometriotic Implants in Administration of Kebar Grass Extract (Biophytum petersianum) and Green Tea Extract (Camelia sinensis) to Mice - Yuli Trisetiyono; Noor Pramono; Syarief Thaufik Hidayat; Widjiati Widjiati (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
The pathological pathway of endometriosis remains unclear and involves complex etiologies. Increased oxidative stress is understood to be related to this disease. Oxidative stress produces reactive oxygen species, causes inflammation that is characterized by recruiting lymphocytes and phagocyte activation, produces cytokines that induce oxidation enzyme, and supports epithelium growth. Oxidative stress conjointly will increase angiogenesis and promotes the proliferation of endometriosis tissue within the peritoneal cavity. Kebar grass and green tea contain high antioxidants, are expected to extend antioxidant defense leading to reduced oxidative stress, inflammation, angiogenesis, and reduced endometriosis tissue implants. The objective is to analyze the consequences of Kebar grass and green tea extract to MDA serum level, TNF-α, and VEGF expression, and the area of the endometriotic implants in the mice models. The study was an experiment designed. It has been conducted within the Department of Obstetrics Gynecology, Faculty of Medicine Diponegoro University and Faculty of Veterinary Medicine Airlangga University. Twenty-one mice were divided into three groups, i.e., the first group of mouse models was given Kebar extract 3 mg/day; the second group was assigned green tea extract 1.1 mg/day; therefore the third group was a control group contains the untreated endometriosis mice. Each treatment was given for fourteen days. MDA serum level was measured by specto-photometric examination, the area of the endometriotic implants was measured by computer tracing technique, whereas TNF-α and VEGF expression of endometriotic implants were measured by IHC using Rammele Scale Index (ImmunoReactive Score). The MDA serum levels of the groups treated with Kebar grass extract and green tea extract were significantly lower than the control group (0.09±0.022 mmol, 0.07±0.019 mmol, and 0.30±0.062 mmol, respectively; p=0.001). TNF-α expression of the groups supplied with each treatment also lower than the control groups (2.43±1.521, 3.66±1.422, and 7.26±2.898, respectively; p=0.002). However, VEGF expression was not significantly different between Kebar grass extract group, green tea group, and the control (4.34±2.402, 4.57±1.998, 7.40±3.495, respectively; p=0.089). Finally, the area of the endometriotic implants of the mice models administered with all treatment was smaller than the control group (0.01±0.025 mm2, 8.76±18.776 mm2, and 34.80±13.079 mm2, respectively; p=0.003). Conclusion: Kebar grass extract, as well as green tea extract administration to endometriosis model mice, resulted in lower MDA serum level and TNF-α expression, smaller the area of endometriotic implants compared, but not resulted in a significant difference of VEGF expression.